EXPERT PERFORMANCE AND THE PERCEPTION OF TRAINING PRACTICES AMONG SPANISH HAMMER THROWERS - Ruiz Pérez, Luis Miguel; Durán Piqueras, Jesús; Arruza Gabilondo, Joseán (Anales de Psicología / Annals of Psychology, 2007)
The purpose of this study was to investigate how expert ham-mer throwers perceived their training activities. Thirty two Spanish ham-mer throwers participated in this study; all of them were components of the Spanish track and field team. They ranged in age from 14 to 30 years (M= 19). Twenty were male and twelve female. The Perception of Train-ing Activities Questionnaire was used to assess athlete’s perceptions of training. Data were collected during training sessions. Results showed that technical skill training alone and with others, and to talk with the coach were the most relevant activities for all athletes, but gender differences were found in the perceptions of different training activities. One of the conclusiones have to see with the different perceptions that about training activities have athletes in different sports.